0.3–10.0 THz spectra for chosen liquid crystal molecules – simulation and physical properties. (2nd November 2017) - Parka, Janusz; Sielezin, Karol
ABSTRACT: In this work, the terahertz (THz) adsorption spectra in the range between 0.3 THz and 10.0 THz of chosen liquid crystal (LC) molecules were studied by using the density functional theory (DFT) method. The molecular structures of the LC compounds such as: the cyanobiphenyls (nCB), phenylcyclohexanes (nPCH), were optimized and calculated by using Molecular Modeling Software Scigress package with standard procedure DFT with functional B88-LYP and basis sets DZVP. The result suggests that the DFT method could be used to calculate refraction index and dealing with the anisotropic nematic liquid crystal (NLC) compounds.